Listeriosis: Bridging the Gap with Integrated Surveillance Among Livestock and Humans - Gharat, Vaibhav (International Journal of Medical Research, 2024)
Listeria monocytogenes, a Gram-positive bacillus, remains a critical public health challenge due to its zoonotic potential and environmental ubiquity. This pathogen causes listeriosis, a severe foodborne disease with high mortality rates, particularly in immunocompromised individuals, neonates, and pregnant women. This article examines the epidemiology of listeriosis and emphasizes the necessity of integrated surveillance frameworks that address its transmission across livestock, humans, and the environment. By adopting the One Health approach, integrated surveillance leverages molecular epidemiology, whole-genome sequencing (WGS), and environmental monitoring to track outbreaks and elucidate transmission dynamics. Livestock surveillance, encompassing routine sampling and genomic characterization, serves as a foundation for early detection, while human surveillance integrates clinical diagnostics and outbreak investigations through real-time data sharing networks. Environmental surveillance further complements these efforts by identifying ecological niches that sustain the pathogen. Despite significant advancements, challenges such as resource constraints and antimicrobial resistance underscore the need for enhanced laboratory infrastructure and interdisciplinary collaboration. This article underscores the importance of integrated surveillance in mitigating the public health impact of Listeria outbreaks and advancing global health security.